Nitrogen in the defense system of Annona emarginata (Schltdl.) H. Rainer - Campos, Felipe Girotto [UNESP]; Ribeiro Vieira, Maria Aparecida [UNESP]; Esteves Amaro, Amanda Cristina [UNESP]; delaCruz-Chacón, Iván; Marques, Marcia Ortiz Mayo; Ferreira, Gisela [UNESP]; Fernandes Boaro, Carmen Sílvia [UNESP] (Public Library of Science (PLoS), 2019)
The concentration of nitrogen can generate different strategies in plants in response to stress. In this study, we investigated how nitrogen concentration interferes with the defense system of Annona emarginata. Low concentrations of nitrogen increased the allocation of photosynthetic resources to carbon metabolism, resulting in an increase in the synthesis of volatile substances involved in signaling and defense that contributed to antioxidant enzymes in overcoming stress. The availability of nitrogen at 5.62 mM concentration might have helped to induce increased resistance in the plants because at this concentration, signaling substances and defense substances (monoterpenes and sesquiterpenes) were observed. Plants cultivated with the highest nitrate concentration displaced energy for the reduction of this ion, likely forming nitric oxide, a signaling molecule. This condition, together with the decrease in carbon skeletons, may have contributed to the lower synthesis of volatile substances of the specialized metabolism that are also involved with signaling. Varying the nitrogen in Annona emarginata cultivation revealed that depending on the concentration, volatile substances show higher or lower synthesis and participation in the system of signaling and defense in the plant. These results may suggest that volatile substances participate in resistance to pests and diseases, which is a necessary condition for Annona emarginata to be preferentially used as rootstock for Annona x atemoya.